All necessary measures? The United Nations and international intervention in Libya - Martin, Ian. (London Hurst and Company, 2022)
Successive governments failed to establish authority over the ever-proliferating armed groups; divisions among regions and cities, Islamists and others, split the country into rival administrations and exploded into civil war; external intervention escalated. Ian Martin gives his first-hand view of the questions raised by the international mission. Was it a justified response to the threat against civilians? What brought about the Security Council resolutions, including authorising military action? How did NATO act upon that authorisation? What role did Special Forces operations play in the rebels' victory? Was a peaceful political settlement ever possible? What post-conflict planning was undertaken, and should or could there have been a major peacekeeping or stabilisation mission during the transition?
Includes index
Keywords: Libya